2022
DOI: 10.3389/fimmu.2022.963931
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of immune response mechanisms in cadmium and copper co-exposed juvenile golden cuttlefish (Sepia esculenta) based on transcriptome profiling

Abstract: Sepia esculenta is a popular economic cephalopod with high yield, delicious meat, and rich nutrition. With the rapid development of heavy industry and medical industry, a large amount of waste has been released into the ocean recklessly in recent years, inducing a significant increase in the content of heavy metals, especially cadmium (Cd) and copper (Cu), in the ocean. This phenomenon significantly affects the growth and development of S. esculenta, causing a serious blow to its artificial breeding. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 118 publications
0
4
0
Order By: Relevance
“…The described biological processes may be significant factors in larval stress following high temperature exposure. In addition, among the 20 significantly enriched KEGG signaling pathways, the PI3K-Akt signaling pathway and MAPK signaling pathway play a crucial role in mollusk immunity ( Song et al, 2005 ; Kharchenko et al, 2010 ; Vergadi et al, 2017 ; Wang et al, 2019 ; Qiao et al, 2021 ; Bao et al, 2022a ). The immune response of S. esculenta larvae might be activated to protect against the injury caused by high temperature exposure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The described biological processes may be significant factors in larval stress following high temperature exposure. In addition, among the 20 significantly enriched KEGG signaling pathways, the PI3K-Akt signaling pathway and MAPK signaling pathway play a crucial role in mollusk immunity ( Song et al, 2005 ; Kharchenko et al, 2010 ; Vergadi et al, 2017 ; Wang et al, 2019 ; Qiao et al, 2021 ; Bao et al, 2022a ). The immune response of S. esculenta larvae might be activated to protect against the injury caused by high temperature exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K-Akt signaling pathway plays a central role in immune regulation by controlling the proliferation, differentiation, and migration of immune cells ( Song et al, 2005 ; Vergadi et al, 2017 ; Bao et al, 2022a ). Previous studies have shown that the PI3K-Akt signaling pathway in mollusks is involved in and regulates immune processes ( Canesi et al, 2002 ; Fukao and Koyasu, 2003 ; Troutman et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…About four weeks later, larvae were hatched and divided into the control group (C) and the Cu-exposed group (Cu). According to the relevant research results from our laboratory on S. esculenta [34,35], 50 µg/L of Cu was produced by dissolution of CuCl 2 × H 2 O 2 powder with 99% AR was used to expose larvae. We collected larvae at 0 h (C_0 h), 4 h (C_4 h and Cu_4 h), and 24 h (C_24 h and Cu_24 h).…”
Section: S Esculenta Larvae and Exposurementioning
confidence: 99%
“…High-throughput transcriptome sequencing is a technology that has developed relatively rapidly. The analysis of organism activities has become more accurate and efficient using this technology [8][9][10]. Previous studies have used this technique to examine biological processes in mollusks.…”
Section: Introductionmentioning
confidence: 99%